Atomic Mineral Characteristics of Indonesian Osteoporosis by High-Resolution Inductively Coupled Plasma Mass Spectrometry. (23rd January 2012) - Noor, Zairin; Sumitro, Sutiman Bambang; Hidayat, Mohammad; Rahim, Agus Hadian; Sabarudin, Akhmad; Umemura, Tomonari
Abstract : Clinical research indicates that negative calcium balance is associated with low bone mass, rapid bone loss, and high fracture rates. However, some studies revealed that not only calcium is involved in bone strengthening as risk factor of fracture osteoporosis. Thus, in this report, the difference of metallic and nonmetallic elements in osteoporosis and normal bones was studied by high-resolution inductively coupled plasma mass spectrometry (HR-ICP-MS). The influence of these elements on bone metabolic processes is also discussed. Inclusion criteria of bone samples consist of postmenopausal woman, trabecular bone fracture, normal and osteoporosis BMD value, and no history of previous disease. The results showed that the concentration of B, Al, S, V, Co, Mo, Te, Ba, La, Ni, As, and Ca/P ratio is higher in osteoporosis than normal. These atomic minerals have negative role to imbalance between bone resorption and bone formation activity. Conversely, concentrations of Na, Mg, P, K, Ca, Cr, Pd, Ag, Mn, Fe, Cu, Zn, Rb, Sr, Pb, and Se are lower in osteoporosis than in normal bones. Among these atoms, known to have important roles in bone structure, we found involvement of atomic mineral and calcium which are considerable to contribute to osteoporotic phenomena.